Coding for Young Learners: Enhancing Computational Thinking and Creativity in Elementary Education - Hilmiyah; Muhith, Abd; Bahri, Syamsul (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
Coding skills have become essential for young learners to develop computational thinking and creativity. This study explores the implementation of coding education to enhance computational thinking among elementary school students, particularly at SD Negeri 21 Dauh Puri Denpasar, where technological access is limited. A case study approach was applied with 28 fifth-grade students. Data were collected through observations, interviews, documentation, and questionnaires. Findings revealed increased computational thinking scores from 56.3 to 74.8 after Scratch-based coding lessons. Significant improvements were observed in decomposition, pattern recognition, and algorithmic thinking, although abstraction remained challenging. Students demonstrated high enthusiasm, especially in creating animations and games. However, limited infrastructure and insufficient teacher training hindered optimal implementation. The study concludes that coding education can foster students' critical thinking and creativity but must be supported by structured teacher training and adequate technological resources. It recommends developing innovative and sustainable learning strategies to make coding an integral part of the elementary education curriculum in Indonesia.